Soybean was sensitive to short-term waterlogged condition at full-pod stage causing yield loss with nitrogen deficiency - Ryota Kurose; Seiya Tanaka; Suguru Horikawa; Yuki Yonekawa; Shodai Noriyuki; Takatoshi Taniguchi; Norimitsu Hamaoka; Chetphilin Suriyasak; Yushi Ishibashi (Plant Production Science)
We analysed the effects of waterlogging during different reproductive stages in soybean. Short-term waterlogged condition at the full pod and beginning seed stages was the strong for decreasing yield with less pod number. The yield loss by waterlogged conditions was mainly caused by decreasing pod number. Additionally, soybean plants under waterlogged conditions decreased photosynthesis rate and the number of nodules. The expression of GmATG8c, autophagy-related gene, increased after waterlogged conditions. Foliar nitrogen application after waterlogged conditions mitigated yield loss. Photosynthetic rate was restored by foliar nitrogen application, but the number of nodules was not recovered. The expression of GmATG8c induced by waterlogged conditions was restored to control after the application. Taken together, soybean was the most sensitive to waterlogging at R4, leading to yield loss with decreasing in pod number.